New diagnostic approach to central hypothyroidism after traumatic brain injury in children and adolescents - Geraldo Miranda Graca; Luiz Roberto Aguiar; Luiz De Lacerda (European Thyroid Journal)
Background: Pituitary lesions after traumatic brain injury (TBI) are frequent in children and adolescents, but the rate of post-TBI central hypothyroidism remains uncertain. Objective: To identify the long-term incidence of post-TBI CH and the clinical and laboratory characteristics of this complication in children and adolescents. Methods: The analysis included 31 patients with a history of TBI with at least 1 year of follow-up. Patients were evaluated at hospital admission and every 3 months thereafter. Assessments included clinical evaluation, brain CT and hormone assessments (basal fT4, IGF-1, cortisol and adrenocorticotropic hormone; insulin tolerance test/thyrotropin-releasing hormone test with TSH, growth hormone and cortisol measurement; and corticotropin-releasing hormone test, if indicated). The CH diagnosis was based on clinical and laboratory findings and a therapeutic trial with levothyroxine. Results: Overall, five patients (16%) developed CH (3 with associated adrenal insufficiency). At 3 and 12 months, median fT4 values were lower in patients with CH compared with those without anterior pituitary dysfunction (n = 18; P = 0.01). Patients with CH received levothyroxine and progressed with clinical resolution and increased median fT4 (from 0.92 to 1.47 ng/dL) and IGF-1 (from −2.08 to −0.22 standard deviation scores (SDS)) levels. Temporary suspension of levothyroxine was accompanied by decreased median fT4 (1.02 ng/dL) and IGF-1 (−1.07 SDS) levels and reappearance of clinical symptoms, which resolved once levothyroxine was reinitiated. Conclusions: The longer follow-up, valorization of clinical manifestations, nontraditional laboratory approach and therapeutic trial with levothyroxine in the present study revealed a higher rate of post-TBI CH in children and adolescents than that reported in the literature.